Just Peace and Presumptive Benefit: Using Fair Play Theory to Explain Political Obligation to Provisional Authority Arrangements - Lacourse, Kevin Philip (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Political Science, 2021)
In March 2003, a coalition of western military powers invaded Iraq. By 9 April 2003, the government of Iraq, led by Saddam Hussein, had been deposed. As a result, from April 2003 through June 2004, Iraq was not a truly sovereign state. Instead during this time, Iraq was governed by an entity known as the Coalition Provisional Authority (C.P.A.). The C.P.A. held supreme executive, legislative, and judicial authority in Iraq. American and British forces unilaterally instituted the C.P.A. and selected the individuals who would administer it without input from any Iraqi citizens. The C.P.A. is just one example of a novel type of political institution called a provisional authority arrangement; other notable examples include the United Nations Transitional Authority in East Timor (U.N.T.A.E.T.). These arrangements raise an interesting question namely, can an individual owe political obligation to a provisional authority arrangement? This is a question which exiting theories of political obligation do not address. The reason for this is that the discipline of political obligation develops to explain the Westphalian state. As a result, provisional authority arrangements are beyond the traditional scope of the discipline of political obligation. Although provisional authority arrangements are indistinguishable from the state in the power that they hold these arrangements differ from the state in that they are foreign to the populations which they govern. Therefore, a provisional authority arrangement seemingly infringes on state sovereignty and violates the principle of non-intervention. This appears to make this type of institution illegal under international law. This dissertation will solve this problem by developing an expanded conception political obligation which accounts for institutions like provisional authority arrangements. It will do this by first establishing what it means for an individual to have political obligation and how political obligation is acquired in the case of the Westphalian state. The project will review four of the most prominent and promising theories of political obligation namely fair play theory, consent theory, associative duties theory, and natural duties theory. Of these accounts, fair play theory is uniquely able to explain why an individual has an obligation to obey the law because it is the law. To the extent that the three other theories succeed in explaining political obligation they each become indistinguishable from fair play theory. The essential thrust of fair play theory is equality via reciprocity; it is wrong to benefit from the sacrifices of others without incurring a similar sacrifice yourself. The theory argues that the state is the institution that provides and protects presumptive public goods. Presumptive public goods are goods that are presumptively beneficial and non-excludable. This is to say that presumptive public goods are goods that are indispensable to the welfare of a community and cannot be provided to some individuals but denied to others. Examples of such goods include rule of law and clean air (amongst others). The quality of presumptive benefit generates a reason for these goods to be provided. On the other hand, the quality of non-excludability means that if an individual receives these goods but does not obey the laws which allow for the provision of these goods, he has created a unilateral and unequal arrangement between him and his fellow citizens. Thus, an individual has an obligation of fair play to follow the laws of the state of which he is a citizen. The second part of this dissertation will demonstrate how fair play theory can be applied to the case of a provisional authority arrangement. The purpose of a provisional authority arrangement is to establish a just peace following war or prolonged military occupation. A just peace, as defined by Brain Orend, involves restoring and vindicating both individual and communal rights which were violated during a war and making these rights more secure than they were ante bellum. A just peace is not something that will arise organically. Instead, a just peace is the product of deliberate coordination. The rights restoration, vindication, and security which are provided by a just peace are both indispensable to the welfare of a community and cannot be provided to some while being denied to others. Consequently, a just peace can be characterized as a presumptive public good. As with other presumptive public goods, the quality of presumptive benefit justifies the provision of a just peace. Nevertheless, an institution is necessary for a just peace to be provided. It is possible for war to end without any preexisting institutions in place and for a population to lack the capacity to enact new institutions for themselves post bellum. When a population lacks the ability to effectively self-govern the foreign character of a provisional authority arrangement is unavoidable. Accordingly, fair play theory can be used to explain political obligation to a provisional authority arrangement such as the C.P.A or the U.N.T.A.E.T.
APPROVED
Keywords: Political Obligation; Just War Theory; Political Theory